E-Commerce in Strengthening The Economy During The Covid-19 Pandemic: A Historical Review - Arelia Dianda; Moses Glorino Rumambo Pandin (Universitas Warmadewa, 2021)
The Covid-19 pandemic bears some resemblance to the Spanish Flu outbreak that occurred in the 20th century. The impact of the Covid-19 pandemic has its own way of dealing with it, for example, there are application sites that can accommodate micro and small entrepreneurs who are affected by Covid-19, namely e-commerce. This study aims to examine the role of e-commerce in strengthening the economy during the Covid-19 pandemic and review it from a historical perspective. This study used a qualitative descriptive method, meanwhile the data of this study data consisting of 19 articles and 1 website. The results of this study revealed that there is an increase in the number of e-commerce access during the Covid-19 pandemic. This shows that e-commerce can help the community in several aspects, one of which is strengthening economic aspects during the Covid-19 pandemic. In addition, there are similarities between the current pandemic situation and the Spanish Flu outbreak experienced during the Dutch colonial period. This research is expected to be a reference for people who want to know about the role of e-commerce during the pandemic.